Vestibular Neuritis - Jeong, Seong-Hae; Kim, Hyo-Jung; Kim, Ji-Soo (Seminars in Neurology, 2013)
Vestibular neuritis is the most common cause of acute spontaneous vertigo. Vestibular neuritis is ascribed to acute unilateral loss of vestibular function, probably due to reactivation of herpes simplex virus in the vestibular ganglia. The diagnostic hallmarks of vestibular neuritis are spontaneous horizontal-torsional nystagmus beating away from the lesion side, abnormal head impulse test for the involved semicircular canals, ipsilesional caloric paresis, decreased responses of vestibular-evoked myogenic potentials during stimulation of the affected ear, and unsteadiness with a falling tendency toward the lesion side. Vestibular neuritis preferentially involves the superior vestibular labyrinth and its afferents. Accordingly, the function of the posterior semicircular canal and saccule, which constitute the inferior vestibular labyrinth, is mostly spared in vestibular neuritis. However, because the rare subtype of inferior vestibular neuritis lacks the typical features of vestibular neuritis, it may be misdiagnosed as a central vestibular disorder. Even in the patient with the typical pattern of spontaneous nystagmus observed in vestibular neuritis, brain imaging is indicated when the patient has unprecedented headache, negative head impulse test, severe unsteadiness, or no recovery within 1 to 2 days. Symptomatic medication is indicated only during the acute phase to relieve the vertigo and nausea/vomiting. Vestibular rehabilitation hastens the recovery. The efficacy of topical and systemic steroids requires further validation.
Keywords: vestibular neuritis; vertigo; nystagmus; head impulse test; vestibular evoked myogenic potential